Giant inflammatory linear verrucous epidermal nevus: Successfully treated with full thickness excision and skin grafting - Binodini Behera; Basanti Devi; Bibhuti B Nayak; Bharti Sahu; Bhabani Singh; Manas R Puhan (Wolters Kluwer Medknow Publications, 2013)
Inflammatory linear verrucous epidermal nevus (ILVEN) is a pruritic, erythematous scaly epidermal nevus which follows a Blaschko's lines. Lichen striatus, linear Darier disease, linear porokeratosis, linear lichen planus, linear psoriasis, and the verrucous stage of incontinentia pigmenti may all have similar clinical presentations as the linear verrucous epidermal nevus. ILVEN can be distinguished from true nevoid psoriasis by pruritus and lack of response to antipsoriatic treatments. Various therapeutic modalities have been described, but no one therapy has been successful consistently. Though giant ILVEN is a relative contraindication to surgical excision, here we report a case showing effectiveness of full thickness excision and skin grafting for this condition.